1998
DOI: 10.1002/bbpc.19981020603
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast relaxation dynamics of solvated electrons in water

Abstract: The relaxation dynamics of excess electrons in a water jet between 5 and 70°C have been investigated on an ultrashort timescale. We have probed the transient absorption of the system immediately after W multiphoton-ionization with a 266 nm ultrashort laser pulse and a time resolution of about 50 fs. Robe wavelengths ranging from 450 to loo0 nm have been provided by a generated white-light continuum. The data suggest a superposition of geminate recombination of the solvated electrons with their original counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
69
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 31 publications
11
69
0
Order By: Relevance
“…3 Since liquid water contains no preexisting cavities, the ejected electron must force significant local solvent reorganization, explaining the marked spectral shifts observed following both CTTS excitation of aqueous iodide 4,9 and the multiphoton ionization of neat water. 4,65,68 We propose that the CTTS dynamics of I -in THF are sensibly explained if the single s-like CTTS excited state lies relatively high in the manifold of disjoint states energetically, as suggested at the center of Figure 7. Thus, CTTS excitation of I -in THF leads to rapid nonadiabatic coupling to disjoint states (as depicted by the wiggly green arrow in Figure 7), such that few electrons relax to their ground states near their iodine atom partners.…”
Section: Discussion: Understanding the Roles Of The Solute And Somentioning
confidence: 81%
“…3 Since liquid water contains no preexisting cavities, the ejected electron must force significant local solvent reorganization, explaining the marked spectral shifts observed following both CTTS excitation of aqueous iodide 4,9 and the multiphoton ionization of neat water. 4,65,68 We propose that the CTTS dynamics of I -in THF are sensibly explained if the single s-like CTTS excited state lies relatively high in the manifold of disjoint states energetically, as suggested at the center of Figure 7. Thus, CTTS excitation of I -in THF leads to rapid nonadiabatic coupling to disjoint states (as depicted by the wiggly green arrow in Figure 7), such that few electrons relax to their ground states near their iodine atom partners.…”
Section: Discussion: Understanding the Roles Of The Solute And Somentioning
confidence: 81%
“…A recent femtosecond study on ultrafast relaxation dynamics of electrons produced by UV-photolysis in a water jet has shown that at present no other transient states than 'hot' solvated electrons are necessary to understand ultrafast dynamics for times t Ն 300 fs [23]. In other words there is a continuous transition from the 'hot' hydrated electron to the wellknown equilibrated hydrated electron.…”
Section: Some Comments On the 'Incompletely Relaxed Electron'mentioning
confidence: 98%
“…Values for the larger isomer I clusters are proportional to 20 The observed fast relaxation, dynamical isotope effects, absence of solvent dynamics upon photoexcitation, and extrapolation to ultrafast IC rate of 50 fs are consistent with the "nonadiabatic" relaxation mechanism of the bulk hydrated electron. 11,12 According to this mechanism, IC occurs on an ultrafast 50 fs time scale, followed by a two-step solvent relaxation on the longer ∼300 fs and ∼1 ps time scales. Further support for the assignment of the latter lifetimes to solvent dynamics comes from measurements by Paik et al, 37 who found biexponential ground-state relaxation with lifetimes of ∼380 fs and 2-10 ps following IC in clusters with 15 e n e…”
Section: Dynamics Of Electron Solvation In Molecular Clusters Ehrler mentioning
confidence: 99%